Microneedle technology on dermatological application - Ning, Xiaoyu (Nanyang Technological University, 2023)
Microneedles (MNs), with its numerous advantages over the traditional transdermal drug delivery approaches, represent a cutting-edge and idea-inspiring technology in the field of biomedical engineering. Over the past decades, great achievements have been made on the optimization of the MNs’ fabrication techniques, expending the various features of the MNs and generation of the MNs with multiple functions. MN is an innovative transdermal drug delivery strategy that overcome the limitations from invasive or inefficient conventional approaches. It create micropores on the skin in a non-invasive and painless manner to aid the efficient delivery of the therapeutics across the skin. Additionally, biomarker sampling and detection by accessing the skin interstitial fluid (ISF) is also achievable by swelling MNs with incorporated sensors. In this thesis, the application of MNs for Chinese herb herbal medicine extract delivery is proposed and demonstrated. Specifically, Chinese herb herbal medicine extract could be premixed with dissolvable polymers and made into MNs through micro-molding. The fabricated drug loaded MNs possess good mechanical strength for human skin penetration. The delivering of the Chinese herb herbal medicine extract via MN to hypertrophic scar fibroblast showed unaffected therapeutic efficiency and localized treatment effect. Additionally, a versatile drug coating methodology is proposed and discussed. In such methodology, drug solution is spray coated onto the frozen MNs and solidified upon contact with the cold MNs’ surface. Subsequent lyophilization could fix the solid drug on the surface of the MNs without affecting the properties of the MN core. As a proof of concept, insulin was coated onto swellable MNs for simultaneously diabetic treatment and glucose sampling. In a more advanced design, the MNs are made from bubble-generating materials which could help to deliver therapeutics deeper and more efficiently into the skin. Incorporating with ultrasound technology, the bubble-generating MNs show advances in delivering both small and big molecules that are frozen coated on the surface of MNs into the mice skin. Moreover, it is demonstrated that the delivering of photosensitizer into the tumor bearing-mouse through the skin by bubble-generating MNs and ultrasound synergistically enhance the penetration and subsequent therapeutic efficiency. Aside from maintaining the MN core properties, the efficiency of therapeutics, when coated onto the MN via the above-mentioned technology could be retained due to the fast fabrication process and low temperature condition that prevent the drug from being degraded or oxidized. Moreover, the therapeutics are in solid state after lyophilization, which further guaranteed their stability. Such property makes the frozen coating strategy a versatile strategy for incorporating various of therapeutics with various types of MNs depending on the application. In conclusion, a facile, versatile drug coating strategy to make functional MNs is introduced in this thesis. Such strategy has the potential for wide range of biomedical applications including controlled drug delivery, multiple drug delivery, biosensing and monitoring.